Regulatory Compliance among Religious Radio Stations in West Java - Ismail, Nurzali; Basith, Achmad Abdul; Hidayat, Dadang Rahmat; Supardi, Supardi (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2026)
Background: Radio broadcasting institutions operating under the legal framework are required to comply with all applicable regulations. Indonesia has established legal provisions that specifically govern the broadcasting system. To date, no article has examined the stance of religious radio stations in West Java on broadcasting regulations. Purpose: This study was conducted to examine the extent to which religious radio stations in West Java comply with existing regulations. Additionally, it aims to shed light on various phenomena, ranging from compliance to violations occurring at religious radio stations in West Java. Methods: This study used a qualitative multi-case study. Data were obtained through observation, interviews, and a review of documents from West Java Regional Indonesian Broadcasting Commission (KPID Jabar). These data were then processed and analyzed to evaluate regulatory compliance among 18 radio stations, utilizing an analysis grounded in law, communication ethics theory, the journalistic code of ethics, and the nine elements of journalism. Results: Based on the research findings, four violations were identified in this phenomenon: restrictions on women’s voices, the temporary suspension of the broadcast of the national anthem “Indonesia Raya,” funding sources that do not comply with regulations or rely on donations, and promotions made in the name of specific groups. Conclusion: Some religious radio stations in West Java have not fully complied with applicable regulations. Implications: These findings suggest that strict oversight is necessary, along with a strong commitment by radio stations to comply with government-established regulations.